"The people who are out of 'right' English": Japanese university students' social evaluations of English language diversity and the internationalisation of Japanese higher education. (28th May 2015) - McKenzie, Robert M.; Gilmore, Alexander
Abstract : Previous research indicates that evaluations of speech forms reflect stereotypes of, and attitudes towards, the perceived group(s) of speakers of the language/variety under consideration. This study, employing both implicit and explicit attitude measures, investigates 158 Japanese university students' perceptions of forms of UK, US, Japanese, Chinese, Thai and Indian English speech. The results show a general convergence between students' explicit and implicit attitudes, for instance, regarding US and UK English as the most correct, and solidarity with Japanese speakers of English. The findings are discussed in relation to intergroup relations between the traditional Japanese cohort and specific groups of overseas students, particularly in light of recent internationalisation policies adopted by many Japanese universities, and the resultant increase in international students from South and East Asia.